SIRT1 polymorphism, long-term survival and glucose tolerance in the general population. - Sylwia M Figarska; Judith M Vonk; H Marike Boezen (PLoS ONE, 2013)
Mutations that increase activity of Sir2 (silent information regulator 2) are associated with extended lifespan of yeast, fruit flies and worms. SIRT1, the human homolog of Sir2, that controls numerous physiological processes including the glucose metabolism, is considered a candidate gene for predicting variation in human lifespan. Whereas the role of Sir2 has been extensively investigated in model organisms, less is known about the relation between SIRT1 and lifespan in humans. In the current study we included 1,390 subjects from a general population-based cohort with 18 years of follow-up to investigate associations between variation in single nucleotide polymorphisms (SNPs) in the SIRT1 gene and human survival. Additionally in 535 male subjects with available data we investigated associations between SIRT1 and glucose tolerance. Carriers of the minor allele of rs12778366 had a significantly reduced mortality risk compared to the wild types: Hazard Ratio 0.69 (95% CI 0.50 to 0.96; p = 0.025). The directions of the effect were the same in females and males, never and ever smokers and the effect was significantly protective in overweight/obese subjects. Carriers of the minor allele of SNP rs12778366 had better glucose tolerance indicated by 0.34 mmol/l lower glucose levels compared to wild type subjects (p = 0.03). This study shows that SIRT1 affects human long-term survival and therefore may be an important factor in modulating lifespan not only in lower organisms, but also in humans.